Strategi PDAM Dalam Peningkatan Pelayanan Air Bersih Di Pulau Bunguran Besar Kabupaten Natun - Suratmojo Suratmojo; Maulana Mukhlis; Etty Puji Lestari (Journal on Education, 2022)
This research was motivated by the existence of several complaints from the public regarding public services in Natuna Regency, especially in terms of clean water services provided by the Tirta Nusa Regional Drinking Water Company, Natuna Regency. People who are customers still complain about the quality of services provided by PDAM. This can lead to a decrease in the number of customers who are dissatisfied with the services provided. The final objective of this study is to determine the service strategy of the Tirta Nusa Regional Drinking Water Company, Natuna Regency. The type of research used is descriptive qualitative. Data collection techniques used in this study were interviews, observation, and documentation. The data analysis technique used a descriptive analysis model. The results of this study are the service strategy of the Regional Drinking Water Company (PDAM) Tirta Nusa, Natuna Regency in terms of empathy (empathy) employees are less concerned with what customers want. The service felt that it was not what they expected. Especially in terms of water services. The strategy used by PDAM Tirta Nusa in improving service quality is to increase clean water services for the population with a minimum coverage of 80%, PDAM Tirta Nusa can increase income by increasing the quantity and quality of clean water services and maintaining the carrying capacity of the surrounding environment